Perlindungan hukum terhadap pembeli lelang yang tidak menerima objek lelang dalam masa penyerahan - Natalia Maria Liju; Abdul Rachmad Budiono (Jurnal Cakrawala Hukum, 2021)
This study discusses what if it turns out that the object of the auction, when its obligations have been paid off by the buyer, is not appropriate? If there is a legal vacuum, then what can be done to protect buyer rights? This research was made in order to answer questions like this, and then to be able to provide legal certainty and also legal protection for the parties involved in the auction. This research method is normative juridical. The approach used is a statutory approach (Statute Approach) and a concept approach (Conceptual Approach). Auction is a direct public sale that has long been known in Indonesia. However, until now the legislation regarding auctions is very minimal. Auctions in Indonesia are still using the Vendu Regulation Number 1908 Number 189, and then directly regulated using the Regulation of the Minister of Finance such as Regulation of the Minister of Finance Number 27 of 2016 concerning Instructions for Auction Implementation. This has resulted in a legal vacuum in some matters regarding auctions. One of them is if the object of the auction submitted during the later delivery is not appropriate. Because this is not regulated in the existing laws and regulations, it results in legal uncertainty for the auction buyer.How to cite item: Liju, N., Budiono, R. (2021). Perlindungan hukum terhadap pembeli lelang yang tidak menerima objek lelang dalam masa penyerahan. Jurnal Cakrawala Hukum, 12(3), 303-313. doi:https://doi.org/10.26905/idjch.v12i3.7095.